2021
DOI: 10.24843/jekt.2021.v14.i01.p07
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Economic Openness, Democracy, and Institutional Quality on Indonesia Exports to ASEAN Plus Three

Abstract: The ASEAN Charter Agreement and the cooperation of the East Asia Free Trade Area ASEAN+3 provide momentum for ASEAN countries to increase economic openness, strengthen the application of democratic principles, and improve institutional quality to enhance trade cooperation. This study aims to explore the role of economic openness, democracy, and institutional quality in increasing Indonesia's exports to ASEAN countries plus three during the 1996-2017 period using the augmented gravity model. The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Purba and Buulolo (2020) observed a more pronounced role of Indonesian exports to ASEAN after the implementation of post-ASEAN Economic Community (AEC) policies. Wikantioso (2021) found that economic openness to trade, democracy, and institutional quality positively impact Indonesia's exports to ASEAN. Regarding Indonesia's trade relations with OIC countries, Sabaruddin (2017) found that Yemen's GDP, political and security uncertainty in Indonesia, and the presence of Indonesian representatives in Yemen significantly affect bilateral trade between the two countries.…”
Section: Empirical Evidence On the Gravity Model And Indonesian Tradementioning
confidence: 99%
“…Purba and Buulolo (2020) observed a more pronounced role of Indonesian exports to ASEAN after the implementation of post-ASEAN Economic Community (AEC) policies. Wikantioso (2021) found that economic openness to trade, democracy, and institutional quality positively impact Indonesia's exports to ASEAN. Regarding Indonesia's trade relations with OIC countries, Sabaruddin (2017) found that Yemen's GDP, political and security uncertainty in Indonesia, and the presence of Indonesian representatives in Yemen significantly affect bilateral trade between the two countries.…”
Section: Empirical Evidence On the Gravity Model And Indonesian Tradementioning
confidence: 99%